2018
DOI: 10.1007/s12664-018-0843-z
|View full text |Cite
|
Sign up to set email alerts
|

Sedation practices in gastrointestinal endoscopy—A survey from southern India

Abstract: Gastrointestinal endoscopies can cause an unpleasant experience for the patient. In India, most endoscopists follow a common institutional policy for sedation. The aim of this study was to analyze the sedation practices in various endoscopy centers across southern India. Data were collected with the help of a structured questionnaire given to a senior endoscopist of the center. Data from the completed questionnaire were later analyzed. Data were obtained from 19 centers across southern India. All endoscopy sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Manual cleaning of endoscopes is being carried out in 46.6 %, and the automatic mode of cleaning in 13.9 % of endoscopy units, with the remainer (39.4 %) using both the methods. A similar practice also was reported in a survey from southern India that was done long before this pandemic [17].…”
Section: Discussionsupporting
confidence: 61%
“…Manual cleaning of endoscopes is being carried out in 46.6 %, and the automatic mode of cleaning in 13.9 % of endoscopy units, with the remainer (39.4 %) using both the methods. A similar practice also was reported in a survey from southern India that was done long before this pandemic [17].…”
Section: Discussionsupporting
confidence: 61%
“…There were 66.4% and 49.1% respondents who reported that their endoscopy centre had no access to airway devices or defibrillators, respectively. These proportions were higher than those in Greece 5 and south India, 7 and may put the patients at risk. In general, both the endoscopist and anaesthesiologist should be alert to the potentially fatal side-effects of endoscopic sedation and should consider safety parameters.…”
Section: Discussionmentioning
confidence: 64%